Automation of the stone materials dosing process, controlled by variable frequency drives - Guillermo Morales-Romero; Nicéforo Trinidad-Loli; Adrián Quispe-Andía; Beatriz Caycho-Salas; Shirley Quispe-Guía; Carlos Palacios-Huaraca; Omar Chamorro-Atalaya (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The objective of this article is to determine to what extent the automation of the stone materials dosing process, controlled by sequential drive of frequency variators, contributes to improving the productivity of a company dedicated to the production of asphalt in Peru for which, initially, the characteristics of the procedure that will lead to achieving the automation will be described. The results will then be displayed with respect to the indicators used to compare productivity before and after automation. The automation will be done by means of the logo 230RE controller, which will be connected to three frequency inverters, the programming development will be through the logo soft comford V8 software, for the sequential actuation, timers with connection delay will be used. Applying the automation, it is possible to improve the annual efficiency by an average of 58.30%, this is reflected in the monthly decrease in production time by 13.92%, in turn increasing the amount of stone material produced by an average of 43.77%. Likewise, it is possible to significantly reduce the production loss capacity by an annual average of 93.99%.